ENDOMETRIOSIS AND FEMALE REPRODUCTIVE HEALTH - A. L. Unanyan (Акушерство, гинекология и репродукция, 2016)
Endometriosis is a pathological process which is characterized by growth and development of tissue resembling the endometrium by its structure and function, while localizing beyond its normal site within the mucous membrane of uterine body. Endometriosis is one of the most topical issues of modern medicine. Regarding mechanisms of endometriosis occurrence, there are various, sometimes mutually exclusive points of view. Thus, over 10 theories of endometriosis origin are known, though none of those can comprehensively explain the multiplicity of manifestation and localization of endometriosis. The lead clinical manifestations of endometriosis are pain syndrome (dysmenorrhea, dyspareunia, dyschezia, etc.) and infertility. One of the main endometriosis treatment methods is surgery, particularly the low-invasive surgery. Surgical methods of treatment are often extra radical for young females and leads to castration syndrome in patients of reproductive and pre-menopausal age, and may well be of low efficacy regardless of surgical tactics. The main principle of medicinal therapy using any hormonal agent is the suppression of estradiol secretion by ovaries. The basis for hormonal therapy is formed by application of progestagens, anti-gestagens and gonadoliberin agonists